HUBUNGAN POWER LENGAN TERHADAP HASIL LARI SPRINT 100 METER PADA SISWA PUTRA SMA NEGERI 1 SUNGAI APIT - Raymond Pratama; Zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Based on field observations that I did at SMA Negeri 1 Sungai Apit, the researcher found that the problem that arose in the field was that the students' running speed was not in accordance with the expected standards. The research objective was to determine the relationship between Arm Power and the results of the 100 meter Sprint run in male students of SMA N 1 Sungai Apit. The population in this study were 10 people, using a total sampling technique, the sample amounted to 10 people. The instrument used was a medicane ball for arm muscle power and a running speed of 100 meters. The data obtained were analyzed using the produck moment correlation. Based on the results of research and data processing using statistical research procedures, it can be concluded that for the relationship between variable x and variable y, the value of r = 0.885 is obtained, then rxy> rtabel is (0.885> 0.666), then Ha is accepted. Key Words: Arm Muscle Power, Running Speed Of 100 Meters